2021
DOI: 10.1097/01.asw.0000744348.32773.b9
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Patients with Colorectal Cancer and a Stoma in China: A Quantitative Cross-sectional Study

Abstract: OBJECTIVE To explore quality of life (QOL) in patients with colorectal cancer and a stoma and factors associated with their QOL. METHODS A quantitative cross-sectional study was carried out in the stoma and wound care clinic of a cancer hospital in China. Participants were recruited from clinic patients. Investigators collected demographic data and clinical information; QOL was measured using a Chinese version of the stoma-QOL scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…7 In other studies evaluating the effects of sleep on the quality of life of individuals with stomas, it has been observed that their sleep scores are low and their quality of life is negatively affected as sleep problems increase. [25][26][27] In this study, the sleep quality of women was found to be worse than that of men (P = .05). In a study by Baldwin and colleagues 11 examining the differences in fatigue and sleep quality of individuals with stomas by gender, women experienced more fatigue and sleep disorders than men within a quality-of-life scale (P = .001).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…7 In other studies evaluating the effects of sleep on the quality of life of individuals with stomas, it has been observed that their sleep scores are low and their quality of life is negatively affected as sleep problems increase. [25][26][27] In this study, the sleep quality of women was found to be worse than that of men (P = .05). In a study by Baldwin and colleagues 11 examining the differences in fatigue and sleep quality of individuals with stomas by gender, women experienced more fatigue and sleep disorders than men within a quality-of-life scale (P = .001).…”
Section: Discussionmentioning
confidence: 46%
“…In research examining the physical dimensions of the quality of life of individuals with stomas, sleep problems were identified as among the most common factors that negatively affected quality of life 7. In other studies evaluating the effects of sleep on the quality of life of individuals with stomas, it has been observed that their sleep scores are low and their quality of life is negatively affected as sleep problems increase 25–27…”
Section: Discussionmentioning
confidence: 99%
“…Improved adaptation and QoL are associated with higher levels of self‐efficacy with ostomy care [30, 32, 33]. Variations in QoL scores can be associated with disparities in care protocols and the availability of ostomy support services [13, 33], with better QoL experienced by those who were satisfied with access to a STN and the quality of care provided [30].…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of lymph node metastases is relatively low, namely 10–20% in pT1-2 colon cancer (CC) [ 4 , 5 ], segmental resections are routinely performed. However, segmental resections result in substantial morbidity [ 6 ], mortality (2.4–3.1%) [ 6 8 ], hospitalisation [ 6 ], and reduction in quality of life (e.g., as a consequence of stomas) [ 9 , 10 ]. Another drawback is that up to 20% of patients with stage I and II CC still develop recurrent disease or distant metastases despite radical segmental resection [ 11 13 ], which could result from insufficient sensitivity of conventional histopathological examination for (micro)metastases [ 12 , 14 ].…”
mentioning
confidence: 99%